Powering Up Developing Countries through Integration? - Auriol, Emmanuelle; Biancini, Sara (Oxford University Press on behalf of the World Bank, 2016)
Power market integration is analyzed in a two-country model with nationally regulated firms and costly public funds. If the generation costs between the two countries are too similar, negative business stealing outweighs efficiency gains so that, subsequent to integration, welfare decreases in both regions. Integration is welfare enhancing when the cost difference between two regions is large enough. The benefits from export profits increase the total welfare in the exporting country, whereas the importing country benefits from a lower price. In this case, market integration also improves incentives to invest compared to autarchy. The investment levels remain inefficient, however, especially for transportation facilities. Free riding reduces incentives to invest in these public-good components of the network, whereas business stealing tends to decrease the capacity to finance new investment.